Simulação do escoamento monofásico em um estágio de uma bomba centrífuga utilizando técnicas de fluidodinâmica computacional - Maitelli, Carla Wilza Souza de Paula (2010)
Oil production and exploration techniques have evolved in the last decades in order to increase fluid flows and optimize how the required equipment are used. The base functioning of Electric Submersible Pumping (ESP) lift method is the use of an electric downhole motor to move a centrifugal pump and transport the fluids to the surface. The Electric Submersible Pumping is an option that has been gaining ground among the methods of Artificial Lift due to the ability to handle a large flow of liquid in onshore and offshore environments. The performance of a well equipped with ESP systems is intrinsically related to the centrifugal pump operation. It is the pump that has the function to turn the motor power into Head. In this present work, a computer model to analyze the three-dimensional flow in a centrifugal pump used in Electric Submersible Pumping has been developed. Through the commercial program, ANSYS® CFX®, initially using water as fluid flow, the geometry and simulation parameters have been defined in order to obtain an approximation of what occurs inside the channels of the impeller and diffuser pump in terms of flow. Three different geometry conditions were initially tested to determine which is most suitable to solving the problem. After choosing the most appropriate geometry, three mesh conditions were analyzed and the obtained values were compared to the experimental characteristic curve of Head provided by the manufacturer. The results have approached the experimental curve, the simulation time and the model convergence were satisfactory if it is considered that the studied problem involves numerical analysis. After the tests with water, oil was used in the simulations. The results were compared to a methodology used in the petroleum industry to correct viscosity. In general, for models with water and oil, the results with single-phase fluids were coherent with the experimental curves and, through three-dimensional computer models, they are a preliminary evaluation for the analysis of the two-phase flow inside the channels of centrifugal pump used in ESP systems